Preliminary assessment of rural airborne microorganisms as emerging environmental hazards: seasonal variability and antimicrobial resistance in South India - Sudan, Harihara A.; Gautam, Sneha; Vincent Sam, Jebadurai S.; Rakshith, Bairi Levi; Asirvatham, Lazarus Godson; Rachel, Esther J.; Subith, D.; Benetta Mercy, A. K.; Henry, Y.; Ho, Chang-Hoi (Frontiers in Environmental Science, 2025)
Airborne microorganisms (bioaerosols) represent hazardous environmental contaminants due to their capacity to replicate, survive in diverse matrices, and disseminate antimicrobial resistance. The sites were selected to represent four distinct rural microenvironments (agricultural, tribal, domestic, and commercial) differing in land use, human activity, and ecological characteristics. Despite increasing evidence from urban and hospital environments, rural bioaerosols remain underexplored, particularly under environmentally relevant conditions where exposure is continuous. Using a MicroBio MB1 air sampler, bacterial concentrations were consistently higher than fungal loads, with winter peaks of 880 colony-forming units (CFU) m−3 in commercial zones and 635 CFU m−3 in tribal sites. In summer, bacterial levels declined overall except in domestic environments (720 CFU m−3), while fungal loads increased, reaching 120 CFU m−3 in domestic sites. Gram staining confirmed the predominance of Gram-positive bacilli and cocci (Bacillus cereus, Staphylococcus), while Lactophenol Cotton Blue staining revealed filamentous fungi, predominantly Aspergillus and Penicillium. Matrix-assisted laser Desorption/Ionization Time-of-flight Mass Spectrometry validated species-level identities, and antimicrobial susceptibility tests showed resistance to erythromycin and amphotericin B, while ciprofloxacin and chloramphenicol remained effective against bacteria, and clotrimazole and fluconazole demonstrated seasonal efficacy against fungi. These results identify rural bioaerosols as critical yet overlooked reservoirs of hazardous microbes and antimicrobial resistance and highlight an urgent need for rural antimicrobial resistance surveillance to support integrated monitoring and public health interventions.